Chemical profile, antioxidant, antimicrobial, and cytotoxic activity of Urtica dioica L. under different cropping and irrigation practices - Chrysargyris, Antonios; Xylia, Panayiota; Kyriakou, Kalia; Papastavropoulou, Konstantina; Gialouris, Panagiotis Loukas P.; Nastou, Eleni S.; Miltiadous, Panagiota; Thomaidis, Nikolaos S.; Proestos, Charalampos; Tzortzakis, Nikos G. (My University, 2025)
Organic agriculture and regulated deficit irrigation (DI) are popular strategies for sustainable agricultural production. The present study investigated organically and conventionally cultivated Urtica dioica (L.) under different irrigation regimes (full and deficit irrigation) in the yield, physiology, phytochemical profile, antimicrobial, and cytotoxic properties under two harvestings periods. Deficit irrigation reduced plant development and yield, but raised dry matter content, especially in plants in organic cultivation. Plants adapted to DI with stomatal closure, while organically grown plants had decreased minerals content, with more profound effects at first harvesting. Plants grown in organic cultivation stimulated hydroxytyrosol and suppressed Rutin levels, compared to conventionally full irrigated plants at the first harvesting. At the second harvesting, Fraxin levels were stimulated, while hydroxytyrosol, chlorogenic acid, and citric acid were decreased with the DI treatment. The DI increased total phenolics, flavonoids, and antioxidants, especially at the first harvest. Plants grown under conventional cultivation had stronger antibacterial activities against Escherichia coli and Staphylococcus aureus. However, plants grown under organic cultivation had stronger cytotoxic properties against two human colorectal cancer cell lines, with more profound effects with the DI applications. Both organic agriculture and DI stimulated biocidal properties with new insights on cultivation management for U. dioica.
Keywords: antioxidant activity; deficit irrigation; minerals; organic cultivation; stringing nettle